WHEN SOCIAL INFLUENCE AND CONSUMER ATTITUDE MATTERS TOWARD ECOLOGICALLY CONSCIOUSCONSUMER BEHAVIOR IN INDONESIA - Muhammad Rizki; Ihsan Hadiansah (President University, 2021)
The paper reviews the ecologically conscious consumer behavior and factor that influenced the ECCB. Since people start to realized environmental issues is very important in their life and many factors that influence. The factors examined in this study consist of Environmental Attitude, Social Influence, and Ecologically Conscious Consumer Behavior. This study uses quantitative methods research design and questionnaire as survey methodology. Sampling technique used non-probability sampling and gather 207 respondents. To analyze the data, this study using regression methods with a simultaneous and partial test. The result showed that the Environmental Attitude has no influence on Ecologically Conscious Consumer Behavior. Meanwhile, social Influence has a positive influence on Ecologically Conscious Consumer Behavior. Both independent variables (Environmental Attitude and Social Influence) have a good influence on the dependent variable (Ecologically Conscious Consumer Behavior) simultaneously. This research gives a better knowledge and understanding of green marketing.Keywords: Environmental Attitude, Social Influence, Ecologically Conscious Consumer Behavior.